Accelerated curing of glued-in threaded rods by means of inductive heating — part IV: curing under low temperatures. Issue 2 (25th January 2022) - Ratsch, N.; Burnett-Barking, M.; Böhm, S.; Voß, M.; Adam, M.; Kaufmann, M.; Vallée, T.
ABSTRACT: Glued-in rods (GiR) are a successful class of structura bonded joints for timber engineering applications. However, they suffer from two limitations: relatively slow curing processes, and requirements related to minimum temperatures for the bonding process. Both, to some extent, limit their wider application, in particular on site. Inductive heating was investigated as a method to overcome both drawbacks by speeding up the process, and enabling it under low temperatures. To verify that, a series of four commercially available adhesives was used to manufacture GiR with beech LVL and Ø16 threaded rods embedded by 100 mm, which were then cured under a variety of conditions. Firstly, cold-curing according to the prescriptions of the technical data sheets and inductively, both at +23°C; secondly, inductively at +5°C; and thirdly, at – 10°C. Numerical modelling complementing these studies allowed for insights related to temperature distributions and curing progress otherwise inaccessible through purely experimental means. The results of this study clearly show that, if selecting appropriate adhesives, curing of glued-in rods is not only accelerated from several days down to a few minutes, but that the process can also be carried at much lower temperatures than those prescribed by the technical datasheets. Based thereupon, a completely new range of practical applications, in which gluing of rods can potentially be made independent of ambient temperatures on-site, has been unleashed.